Neurological and cardiopulmonary manifestations of pulmonary arteriovenous malformations - Lu, Weida; Dai, Honggang; Li, Yunyi; Meng, Xiao (Frontiers in Medicine, 2024)
Pulmonary arteriovenous malformations (PAVMs) are direct pulmonary artery-to-vein connections without pulmonary capillaries that result in intrapulmonary right-to-left blood shunts. Although most patients with PAVMs may be entirely asymptomatic, PAVMs can induce a series of complications involving the neurological, cardiovascular, and respiratory systems that can lead to catastrophic and often fatal clinical sequelae. In this study we review the available literature and summarize the reported PAVM-related complications among patients with PAVMs. The reviewed studies included observational studies, case studies, prospective studies, and cohort studies, and we provide an overview of PAVM-related neurological and cardiopulmonary manifestations, including stroke, cerebral abscess, transient ischemic attack, cerebral hemorrhage, migraine, seizure, dizziness, cardiac failure, arrhythmia, myocardial infarction, cough, hypoxemia, dyspnea, respiratory failure, hemoptysis, and hemothorax. Identifying and treating PAVMs before the presentation of major complication is important because this can prevent the occurrence of complications and can result in better outcomes. PAVM patients should thus be better evaluated and managed by a multidisciplinary team because they may be in a treatable phase prior to their condition becoming life-threatening.